(untitled) (The Agriculturists, 2014)
A total of 887 ducklings of BLRI-1 duck genotype and 352 ducklings of BLRI-2 duck genotype were studied to measure productive and reproductive performances under intensive management. Data were recorded on body weight, egg production, egg weight, fertility, embryonic mortality, hatchability, feed intake, age at sexual maturity, body weight at maturity and egg weight at maturity. The fertility rate in BLRI-1duck was significantly (p<0.01) higher than that of BLRI-2 duck, while hatchability of BLRI-2 duck on fertile eggs were significantly (p<0.05) better compared to BLRI-1 duck. The embryonic mortality was significantly (p<0.01) higher in BLRI-2 duck than BLRI-1 duck. Duckling weight was influenced by egg weight (p<0.05) but difference in duckling: egg ratio was not significant (p>0.05). Hatching weight, 4th week and 12th week of age were significant (p<0.05) influent while the body weight of ducks at 8th week did not differ significantly (p>0.05) for BLRI-1 and BLRI-2 ducks, respectively. The least squares mean for age at sexual maturity were 158 days and 151.75 days, respectively for BLRI-1 and BLRI-2 ducks (p<0.05). BLRI-1 duck started to lay eggs almost one week late compared to BLRI-2 duck. Duck weight at sexual maturity, egg weight at first lay and egg production did not have significant (p>0.05) difference between genotypes. It may be concluded that BLRI-2 duck genotype is superior in terms of hatchability and age at sexual maturity to BLRI-1 duck genotype. DOI: http://dx.doi.org/10.3329/agric.v12i1.19485 The Agriculturists 2014; 12(1) 10-14